Private Equity Fund Size, Investment Size, and Value Creation - Humphery-Jenner, Mark (Review of Finance, 2012)
Abstract This paper examines why large private equity (PE) funds earn lower returns. The article argues that large PE funds are suited to making large investments and small PE funds are suited to nurturing start-ups. Thus, the suboptimal investment in small companies is one driver of the size effect in PE. A theoretical model and empirical results from a sample of 1,222 funds in the USA support this prediction. The largest 25% of PE funds earn internal rates of return of 5.17% when they invest in the largest 25% of companies but only −2.98% when they invest in the smallest 25%. This suggests that investment size is a driver of the size effect in PE.